CRISIS MANAGEMENT STRATEGY OF TEGAL CITY PUBLIC RELATIONS - Rahma Wulandari; Prayudi Prayudi; Subhan Afifi (The Indonesian Journal of Communication Studies, 2019)
The arrest of Tegal Mayor Siti Masitha Soeparno by the Corruption Eradication Commission (KPK) accompanied by negative media coverage undeniably caused a crisis that was able to reduce public trust in the Tegal City Government. This study intends to find out the crisis management and public relations strategy of the Tegal City Government regarding the KPK's Red-Handed Arresting Operation (OTT) against Mayor of Tegal. This study uses a qualitative approach with a case study method. The results of this study indicate that the Government of Tegal City tends to ignore the symptoms or signs of the crisis starting to appear and not immediately respond and make decisions quickly and effectively to reduce the risk of a crisis. Public Relations of the Tegal City Government only conducts public relations routines when a crisis occurs, they do not have good training in handling the crisis so that it is not competent in dealing with crises. Public Relations of the Tegal City Government tends to be indifferent to the crisis experienced by the institution and only focus on routine public relations work such as reporting on government activities or agendas. The Tegal City Government has responded to the crisis and tried to restore public trust and improve the governance system as evidenced by various bureaucratic reforms and improvements in the field of public services. The crisis communication strategy used by the Tegal City Government, that is: corrective action strategy with efforts to improve and preventive efforts, justification strategies shown by the City of Tegal by localizing the crisis, and ingratiation strategies carried out by the Tegal City Government by implementing the National Development Dialogue "Towards Tegal Trustworthy and Blessed "which succeeded in formulating city branding.